Randomized clinical trial of a simple pulmonary recruitment manoeuvre to reduce pain after laparoscopy. Issue 10 (12th August 2013) - Khanna, A.; Sezen, E.; Barlow, A.; Rayt, H.; Finch, J. G.
Abstract : Background: Shoulder tip and abdominal pain following laparoscopic procedures are well recognized causes of postoperative morbidity. In this double‐blind randomized clinical trial attempts were made to reduce postoperative pain in patients undergoing laparoscopic surgery by implementing a simple intraoperative technique . Methods: Patients undergoing elective laparoscopic cholecystectomy or laparoscopic transabdominal preperitoneal inguinal hernia repair were randomized to receive either the current standard treatment (control group) or an intervention to remove residual carbon dioxide. In the intervention group, the pneumoperitoneum was removed at the end of the operation by placing the patient in the Trendelenburg position and utilizing a pulmonary recruitment manoeuvre consisting of two manual inflations to a maximum pressure of 60 cmH2 O. In the control group, residual pneumoperitoneum was evacuated at the end of the procedure by passive decompression via the open operative ports . Results: Seventy‐six randomly assigned patients, 37 in the intervention group and 39 in the control group, were recruited. Overall postoperative pain scores were significantly lower in the intervention group ( P = 0·001). Median (interquartile range) pain scores were significantly lower in the intervention group compared with the control group at both 12 h (3·5 versus 5; P < 0·010) and 24 h (3 versus 4·5; P < 0·010) . Conclusion: Active evacuation of residual pneumoperitoneum following laparoscopic procedures, by means of two pulmonary recruitment manoeuvres in the Trendelenburg position, reduces postoperative pain significantly. This simple and safe technique can be implemented routinely after abdominal laparoscopy. Registration number: NCT01720433 ( http://www.clinical trials.gov) . Abstract : Simple techniques to reduce pain